A Comparison of Hospital and Nonhospital Colonoscopy: Wait Times, Fees and Guideline Adherence to Follow-Up Interval - Noah Ivers; Michael Schwandt; Susan Hum; Danielle Martin; Jill Tinmouth; Nick Pimlott (Canadian Journal of Gastroenterology)
BACKGROUND: Although colonoscopy is increasingly performed in nonhospital facilities, studies to date examining differences between colonoscopy services in hospital and nonhospital settings have been limited, in large part, to administrative databases.